Losers' consent : elections and democratic legitimacy - Anderson, Christopher J. (Oxford ; New York : Oxford University Press, 2005)
"Based on data from democracies across the globe, this book examines how election losers and their supporters respond to their loss and how institutions shape losing"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Legitimacy of governments; Elections; Comparative government